Endoplasmic reticulum chaperone Gp96 controls actomyosin dynamics and protects against pore-forming toxins - Mesquita, FS (2017)
During infection, plasma membrane (PM) blebs protect host cells against bacterial pore-forming toxins (PFTs), but were also proposed to promote pathogen dissemination. However, the details and impact of blebbing regulation during infection remained unclear. Here, we identify the endoplasmic reticulum chaperone Gp96 as a novel regulator of PFT-induced blebbing. Gp96 interacts with non-muscle myosin heavy chain IIA (NMHCIIA) and controls its activity and remodelling, which is required for appropriate coordination of bleb formation and retraction. This mechanism involves NMHCIIA-Gp96 interaction and their recruitment to PM blebs and strongly resembles retraction of uropod-like structures from polarized migrating cells, a process that also promotes NMHCIIA-Gp96 association. Consistently, Gp96 and NMHCIIA not only protect the PM integrity from listeriolysin O (LLO) during infection by Listeria monocytogenes but also affect cytoskeletal organization and cell migration. Finally, we validate the association between Gp96 and NMHCIIA in vivo and show that Gp96 is required to protect hosts from LLO-dependent killing.